Patterns of damage functions: Crop yield loss according to injury from disease and pest at varying attainable yields - Willocquet, Laetitia; Savary, Serge (Plant disease, 2025)
Damage functions, i.e., the relationships between crop yield loss (or relative yield loss) and disease injury provide pivotal quantitative knowledge to inform tactical and strategic decisions for disease management. Damage functions depend on the level of the attainable yield (Ya), i.e., on crop yield in absence of injury. Although well-known, this effect has been poorly documented despite its clear relevance to disease management. Here, the effects of variable Ya on the shapes of damage functions were therefore analysed using the available literature. Damage functions expressed as relative yield loss were analysed on seven major crops for 17 plant pathogens or pests. Two main groups of injuries are distinguished. First, injuries that are associated with several damage mechanisms involving compensation processes, leading to decreased yield-reducing effects of injury as Ya increases. These damage mechanisms are: light stealing, leaf senescence acceleration, reduction of radiation use efficiency, and thinning of crop stand. Second, for injuries that are associated with assimilate diversion, the yield-reducing effect increases as Ya increases. The relationships between actual yield and injury levels at varying Ya were then examined, allowing to (1) derive disease management strategies according to Ya; (2) illustrate how damage functions can be used to establish injury thresholds according to the levels of Ya; and (3) highlight the risk of wrong decisions in disease management, if these decisions are only based on a single damage threshold value determined for a single Ya. The paucity of available literature on the topic calls for further research to quantify damage mechanisms and damage functions at varying Ya on a broader diversity of crop diseases and pests.